Evaluasi Perencanaan dan Distribusi Obat Program di Dinas Kesehatan Provinsi Sulawesi Tenggara - Yuliana Boku; Satibi Satibi; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The development of the health sector is an important concern in the international commitments set out in the Millennium Development Goals (MDGs). One of the indicators is the availability and affordability of drugs. Therefore, good management of drugs is needed. This study aims to evaluate planning and distribution of drug programs in 2017 at the Southeast Sulawesi Provincial Health Office and the factors that influence it. This study was conducted in September – October 2018. The programs’ drugs evaluated were for malaria, leprosy, tuberculosis and Humman Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS). This is a descriptive research with quantitative data obtained retrospectively and qualitative data obtained through observations and interviews with interviewees selected by purposive sampling. The data was analyzed using indicators and then compared with the research results. The results showed that the planning and distribution of the drugs had not been fully in accordance with the standard. It was indicated that there were 8 indicators had not meet the standards, namely the accuracy of planning; planning irregularities; level of drug availability; percentage of drugs expired; percentage of deviations from drugs distributed; Inventory Turn Over Ratio (ITOR); average time of drug emptiness; the percentage of dead drug stock, and there were 7 indicators which had met the standars, namely the drug structuring system; the matching number of real goods with stock; organizational management; responsible person; the number of human resources; and financial and information systems. The factors that influence is team coordination; recording and reporting; and operational funds.